The Effect of Think–Pair–Share on Students’ Reading Comprehension of Descriptive Texts in Indonesian Senior High School - Cinta Nanda Zerenta Pangesti Salma; Junaedi Setiyono; Andrian Nuriza Johan (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study aimed to examine the effect of the Think–Pair–Share (TPS) technique on students’ reading comprehension of descriptive texts among eleventh-grade students at SMA Negeri 5 Purworejo. The study was motivated by the need to promote more interactive and student-centered strategies in reading instruction, particularly in understanding descriptive texts. A quantitative pre-experimental method employing a one-group pre-test and post-test design was used. The participants consisted of 36 students selected through purposive sampling. Data were collected using reading comprehension tests administered before and after the implementation of the TPS technique. The collected data were analyzed using both descriptive and inferential statistics to determine the extent of students’ improvement. The results of the paired sample t-test revealed a statistically significant difference between pre-test and post-test scores (p < 0.05), indicating that the TPS technique had a positive and meaningful effect on students’ reading achievement. The improvement can be attributed to the structured stages of TPS, which require students to think independently, collaborate with peers, and actively share their ideas in class discussions. These stages foster greater engagement, critical thinking, and deeper comprehension of the text. Moreover, the interactive nature of TPS supports students in constructing meaning more effectively through social interaction. Therefore, TPS can be considered an effective and practical instructional strategy for enhancing students’ reading comprehension. This study also contributes to the existing literature by providing empirical evidence on the application of TPS in teaching descriptive texts and offers valuable insights for English teachers seeking to implement collaborative learning approaches in reading classrooms.